2021
DOI: 10.13057/biodiv/d220813
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antioxidant potential of ethyl acetate extract from Streptomyces AIA12 and AIA17 isolated from gut of Chanos chanos

Abstract: Abstract. Kurnianto MA, Kusumaningrum HD, Lioe HN, Chasanah E. 2021. Antibacterial and antioxidant potential of ethyl acetate extract from Streptomyces AIA12 and AIA17 isolated from gut of Chanos chanos. Biodiversitas 22: 3196-3206. Streptomyces has been recognized as a promising and productive source of antibacterial and antioxidant compounds. The phenotypic and genomic characterizations indicated AIA12 and AIA17 are closely related to the S. globisporus ARGB01 and S. misionensis S1-SC15, respectively. Incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…ANOVA followed by Duncan's multiple range test indicated that the growth absorbance of test bacteria exposed to CFS was significantly lower than that of test bacteria not exposed to CFS. This result indicates that the presence of extracellular metabolites produced by Streptomyces in CFS could inhibit the growth of the test bacteria and supports previous findings demonstrating the potential antibacterial properties of metabolites produced by Streptomyces isolated from the gut of C. chanos [ 23 , 24 ]. The difference in antibacterial activity produced is due to differences in the concentration of extracellular metabolites produced [ 13 ].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…ANOVA followed by Duncan's multiple range test indicated that the growth absorbance of test bacteria exposed to CFS was significantly lower than that of test bacteria not exposed to CFS. This result indicates that the presence of extracellular metabolites produced by Streptomyces in CFS could inhibit the growth of the test bacteria and supports previous findings demonstrating the potential antibacterial properties of metabolites produced by Streptomyces isolated from the gut of C. chanos [ 23 , 24 ]. The difference in antibacterial activity produced is due to differences in the concentration of extracellular metabolites produced [ 13 ].…”
Section: Resultssupporting
confidence: 91%
“…Six Streptomyces (i.e., S. variabilis SCA-5, S. variabilis SCA-11, S. variabilis AIA-10, S. labedae SCA-8, S. globisporus AIA-12, and S. misionensis AIA-17) were obtained from the gut of milkfish ( C. chanos ) [ 23 , 24 ]. The strains were identified through their morphological, physiological, biochemical, and molecular characteristics by 16S rRNA gene sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BLIS produced by six Streptomyces isolated from the gut of Chanos chanos: S. variabilis SCA5 (S5), S. variabilis SCA11 (S11), S. variabilis AIA10 (A10), S. labedae SCA8 (S8), S. globisporus AIA12 (A12) and S. misionensis AIA17 (A17) [15][16][17] with the method and culture conditions according to Kurnianto et al [18]. BLIS in freeze-dried form dissolved in distilled water.…”
Section: Fractionation Blis By Gel Filtration Chromatographymentioning
confidence: 99%